A critical reflexive model: Working with life stories in health promotion education - Norton, L.; Sliep, Y. (South African Journal of Higher Education, 2018)
In this paper a critical reflexive model is described and applied to life stories of tertiary education students doing a masters in health promotion. At the heart of the process is the dialogical space where relational reflexivity is facilitated and around which the narrative story is developed. Examples from tertiary education are given to illustrate how working reflexively with life stories increases critical thinking and a sense of identity, belonging and agency. The approach is holistic in that it connects new knowledge to lived experience. It is based on a social constructionist worldview that uses a narrative lens which recognises that our knowledge is continuously constructed in context and in interaction with others. One way to understand ourselves and others is to understand our own and each other’s stories. The model which facilitates this process involves four iterative loops: deconstructing power in the collective; mapping values and identity; negotiating agency; and rendering accountable performance.